Strategi Mitigasi Risiko untuk Menjaga Kesehatan Mental Pelajar di Era Digitalisasi - Rossa Ananda Zuliana; Irsyad, Irsyad; Merika Setiawati (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The development of digital technology has had a significant impact on the modern education system. Although digitalization facilitates the learning process, students also face the risk of mental health disorders due to academic pressure, social media exposure, and technology dependence. This article aims to analyze risk mitigation strategies for maintaining student mental health in the digital era. The method used is a literature review from various academic sources and relevant government policies. The results of this study indicate that the roles of schools, parents, and students are crucial in creating a balance between technology use and psychological well-being. Effective mitigation strategies include digital literacy, strengthening social support, and increasing self-awareness. With the implementation of appropriate strategies, digitalization can be utilized positively without causing negative psychological impacts on students.